Simulation of characteristics of gamma-radiation detectors based on mercury compounds - Skrypnyk, A.I.; Zakharchenko, A.A.; Khazhmuradov, M.A.; Prokhorenko, E.M.; Klepikov, V.F.; Lytvynenko, V.V. (Вопросы атомной науки и техники, 2013)
We used Monte-Carlo method to compare characteristics of HgI₂- and HgS-detectors which work in the mode of pulse amplitude analysis. The GEANT4 Simulation Toolkit version 4.9.4p04 and EGSnrc version 4.r2.3.2 were used for modeling gamma-quantum trajectories and calculating response functions in the gamma-quantum energy range between 25 keV and 3 MeV.We supposed that simulated HgI₂- and HgS-detectors were equipped with planar contacts and their geometric sizes were 3.14 mm² × 1 mm. Basing on calculated detector's response functions, we obtained the efficiency of gamma-quantum registration and detector sensitivity dependence on energy for energy range from 0.025 to 3 MeV. Statistical characteristics of theoretical response functions and amplitude distributions of pulses are studied taking into account noise and incomplete charge collection distortions of theoretical response functions. Results of simulation show that in the high-energy region the efficiency of energy conversion of gamma-quanta in charge signal for HgS detectors can exceed the same characteristic for HgI₂-detectors up to 10. . . 12 percents.